Tensions experienced by employment support professionals when seeking meaningful employment for persons with developmental disabilities. (April 2020) - Rashid, Marghalara; Thompson-Hodgetts, Sandra; Nicholas, David
Abstract: Purpose: Current research suggests that supported employment for people with developmental disabilities offers significantly higher rates of employment, personal satisfaction, and employer satisfaction. This study focuses on tensions experienced by employment support professionals while working with employers regarding employment for persons with developmental disabilities. These tensions experienced by employment support professionals is an area that is currently under researched and needs further exploration. Method: In-depth interviews and focus group sessions were conducted with employment support professionals (n = 34) from a variety of organizations in two Canadian provinces. Theoretical sampling was used to recruit study participants. Data were thematically analysed, informed by a grounded theory approach. Results: Four main themes emerged: (i) Hire for capabilities, not pity, (ii) The bottom line: profit versus moral code, (iii) Education and concerns about accommodations and costs, and (iv) Pros and cons of incentives. Conclusions: Our study highlights some of the tensions experienced by employment support professionals when they work with employers considering employing persons with developmental disabilities. This information can be used to help employment support professionals, and others, target approaches and supports aimed at building employers' capacity to support meaningful employment for people with developmental disabilities.